2006
DOI: 10.1111/j.1740-0929.2006.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Meat characteristics of Qinghai yak and semi‐wild yak

Abstract: Six domestic yaks aged 6 years, comprising three culling male and three culling female yaks, from the Qinghai Lake area and three male semi‐wild yaks aged 6 months from Datong Yak Farm were used to detect the levels of amino acids, mineral elements, residual heavy metals and pesticides in yak meat. The results showed that there was little difference in amino acid levels for different types of yak by age and sex. The meat of the adult male yak was 7.35 mg/kg higher in calcium (P < 0.05) and 124 mg/kg higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The long slaughter cycle (usually 9 years) results in low production of meat and a poor meat quality (Han, Xie, Bi, Liu, & Hu, 2002; Wan et al., 2011). Previous research has reported that the meat of grazing yaks contain favourable amino acid and fatty acid profiles as well as a high protein content, but after cooking, the meat tenderness is poor (Luo, Tong, Wei, & Zhao, 2006). Therefore, yak meat is mostly used to make beef jerky, which limits its development and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The long slaughter cycle (usually 9 years) results in low production of meat and a poor meat quality (Han, Xie, Bi, Liu, & Hu, 2002; Wan et al., 2011). Previous research has reported that the meat of grazing yaks contain favourable amino acid and fatty acid profiles as well as a high protein content, but after cooking, the meat tenderness is poor (Luo, Tong, Wei, & Zhao, 2006). Therefore, yak meat is mostly used to make beef jerky, which limits its development and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Meat of the domestic yak from the harvest of surplus males and unproductive females is critical to sustenance and can provide some income from its sale (Wiener et al 2003;Zhang et al 1994). It is lean, beef-like in flavor, and rich in myoglobins (Wiener et al 2003), but there is no evidence that introducing blood lines of wild yaks into domesticated breeds improves nutrient levels (Luo et al 2006).…”
Section: Husbandrymentioning
confidence: 99%
“…Despite the numerous applications of metabolomics in cattle meat, meat from the other bovine species has been rarely described. Examples can be traced only in the works by Ritota et al [17], who observed buffaloes in relation to bovines, and in the work by Luo et al, who quantified 17 amino acids in the meat of domestic and semi-wild yaks [21]. Moreover, metabolomic investigations have generally observed meat from any bovine species as a matrix with homogenic characteristics, without considering the peculiarities of the different muscles.…”
Section: Introductionmentioning
confidence: 99%